Effects of atorvastatin and metformin on development of pentylenetetrazole-induced seizure in mice - Zeyghami, Mohammad Ali (Heliyon, 2020)
Recent studies have shown that statins and Metformin may have beneficial effects on seizure through different mechanisms. In the current study, we investigated whether Metformin, Atorvastatin, and concomitant uses of them have beneficial effects on pentylenetetrazole (PTZ)-induced kindling. Adult male C57BL/6 mice were randomly divided into four experimental groups with seven mice in each group. Group 1, control group; group 2, received Metformin (200 mg/kg, i.p); group 3, received Atorvastatin (10 mg/kg, i.p.); group 4, received Atorvastatin (10 mg/kg, i.p.) plus Metformin (200 mg/kg, i.p.). Twenty minutes after injection of the mentioned drugs, the experimented mice received 37/5 mg/kg of PTZ intraperitoneally on alternating days. Then the convulsive behavior signs were evaluated for 20 min after each PTZ injection. There were significant differences in the stage 2 latency parameter among group 2 (p = 0.033, F = 8.46)/group 3 (p = 0.032, F = 10.42)/group 4 (p = 0.008, F = 24.57) as compared to the control group, while no significant differences were found comparing only group 2,3, and 4 with eachother excluding the control group. Pretreatment with Atorvastatin (p = 0.002, F = 33), Atorvastatin + Metformin (p = 0.006, F = 20.77), and Metformin alone increased stage 5 latency as compared to the PTZ group, significantly. Also, our results have shown that pretreatment with Atorvastatin (p = 0.013, F = 14.48), Metformin (p = 0.015, F = 16.67), and concomitant usage of them significantly decreased stage 5 duration as compared to the control group. Our findings clearly demonstrate that concomitant use of Metformin and Atorvastatin has no more protective effect against the development of kindling as compare to these drugs alone. Thus, we concluded that, these drugs may inhibit kindling via a similar mechanism and we suggested that it is probably through regulation of autophagy.